SOX18 knockdown inhibits colorectal cancer metastasis and angiogenesis through regulation of SAPK/JNK and PI3K/AKT/mTOR signaling pathways - Deng, Xiao; Shuai, Ping; Liu, Suyun; Zhu, Xiansen; Miao, Zuohua (Journal of Gastrointestinal Oncology, 2026)
Background: Sex determining region Y-box 18 (SOX18) has been found to be overexpressed in several types of tumors. However, the molecular mechanism underlying the biological function of SOX18 in colorectal cancer (CRC) remains unclear. This study aims to investigate the effect of SOX18 gene knockdown on proliferation, invasion, angiogenesis and its relationship to SAPK/JNK and PI3K/AKT/mTOR signaling pathways in CRC cells.Methods: The Cancer Genome Atlas (TCGA)‑CRC dataset was analyzed to assess the clinical correlation of SOX18 expression. SOX18 was knocked down in OUMS‑23 and HCT116 CRC cells. Cell proliferation, migration, invasion, apoptosis, and angiogenesis were evaluated by functional assays. Western blot and quantitative real‑time polymerase chain reaction (qPCR) were used to detect pathway activity. The JNK agonist anisomycin was applied for rescue experiments, while the AKT inhibitor MK‑2206 was used for pathway validation.Results: High SOX18 expression correlated with poor prognosis in CRC patients. SOX18 knockdown significantly inhibited proliferation, migration, invasion, and angiogenesis, while promoting apoptosis in CRC cells and human umbilical vein endothelial cells (HUVECs). Mechanistically, SOX18 silencing suppressed the phosphorylation of JNK, AKT, and mTOR, and downregulated HIF‑1α/VEGF expression. Anisomycinmediated JNK activation selectively restored p‑JNK and fully reversed the tumor‑suppressive and anti‑angiogenic effects of SOX18 knockdown. In contrast, MK‑2206 further inhibited the PI3K/AKT/mTOR pathway without altering JNK activity.Conclusions: SOX18 knockdown suppresses CRC metastasis and angiogenesis by regulating SAPK/JNK and PI3K/AKT/mTOR signaling pathways.